Energy Conservation of Linear Wave Equations on Equilateral Quantum Graphs - Burhan Mohammad Januar Ismail; Soeharyadi Yudi (ITM Web of Conferences)
We study the conservation of energy of the linear wave equation on an equilateral quantum graph. We equipped the quantum graph with Dirichlet and Neumann-Kirchhoff. We also show that the linear wave’s energy conservation remains relevant on the quantum graph. Moreover, our results are any properties of the conservation problem on the quantum graph and simulation that show the energy is conserved using the amplitude of the solution of linear wave equations on each edge.